New Updates in E-Learning - Babulak, Eduard (IntechOpen, 2022)
This book presents state-of-the-art educational technologies and teaching methodologies and discusses future educational philosophies in support of the global academic society. New Updates in E-Learning is a collection of chapters addressing important issues related to effective utilization of the Internet and Cloud Computing, virtual robotics, and real-life application of hybrid educational environments to enhance student learning regardless of geographical location or other constraints. Over ten chapters, the book discusses the current and future evolution of educational technologies and methodologies and the best academic practices in support of providing high-quality education at all academic levels.